1996
DOI: 10.3758/bf03201083
|View full text |Cite
|
Sign up to set email alerts
|

The perception of number from the separability of the stimulus: The Stroop effect revisited

Abstract: The literature on numerical perception is reviewed from the standpoint of research on selective attention, and predictions are made concerning the dimensional interaction between physical and numerical size of numerals. We manipulated stimulus differences to make the classification of numerical value slightly better (Experiment 1), substantially better (Experiment 2), or worse (Experiments 3---4) than classification of physical size. Garner, Stroop, and redundancy effects were used to gauge the degree of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
181
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(201 citation statements)
references
References 82 publications
(112 reference statements)
18
181
2
Order By: Relevance
“…A more convincing finding would be that numerical and non-numerical quantities interact with each other. This is exactly what is found with the size congruity paradigm (Algom et al, 1996;Cohen Kadosh and Henik, 2006;Cohen Kadosh et al, 2007e;Fias et al, 2002;Henik and Tzelgov, 1982;Hurewitz et al, 2006;Pansky and Algom, 1999;Schwarz and Ischebeck, 2003;Tzelgov et al, 1992). In this Stroop-like task, numerical and physical dimensions are varied independently.…”
Section: Similar Effect Patterns With Different Kinds Of Quantity: Thsupporting
confidence: 73%
“…A more convincing finding would be that numerical and non-numerical quantities interact with each other. This is exactly what is found with the size congruity paradigm (Algom et al, 1996;Cohen Kadosh and Henik, 2006;Cohen Kadosh et al, 2007e;Fias et al, 2002;Henik and Tzelgov, 1982;Hurewitz et al, 2006;Pansky and Algom, 1999;Schwarz and Ischebeck, 2003;Tzelgov et al, 1992). In this Stroop-like task, numerical and physical dimensions are varied independently.…”
Section: Similar Effect Patterns With Different Kinds Of Quantity: Thsupporting
confidence: 73%
“…The issue of discriminability is critical to the Garner paradigm because differences in baseline discriminability can cause asymmetries in Garner interference between the two tasks (Algom et al, 1996). According to a speed-of-processing account (e.g., Atkinson et al, 2005;Schweinberger et al, 1999), mismatches in discriminability would cause asymmetric interference patterns because the more discriminable dimension (i.e., emotional facial expressions) is computed before the less discriminable dimension (i.e., gaze direction) has been fully processed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Ganel et al (2005) Experiments 1 and 2, an overall reaction time advantage was observed for gaze judgments over emotion judgments, a finding that is indicative of differences in the discriminability of the two dimensions and that suggests that gaze is being processed more quickly than facial emotion (Algom et al, 1996). Baseline discriminability should be matched in the Garner paradigm; otherwise, differences in discriminability can give rise to asymmetries wherein the less discriminable dimension (in this case, emotion) may be affected more by the more discriminable dimension (gaze).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The disappearance of the semantic process might be attributable to a lower level processing of Kana numbers (see General Discussion). In the indirect task, Kana numbers might be processed as visual objects (Algom, Dekel, & Pansky, 1996;Pansky & Algom, 2002). Otherwise, Kana numbers processing might end at the phonological level (Brysbaert, 2001;Fias, 2001;Fias, Reynvoet, & Brysbaert, 2001).…”
Section: Discussionmentioning
confidence: 99%